AKTIVITAS POLISAKARIDA KRESTIN DARI EKSTRAK Coriolus versicolor TERHADAP PENINGKATAN ANTIBODI Mus musculus AKIBAT PAPARAN Mycobacterium tuberculosis - Sri Puji Astuti Wahyuningsih; Amalia Nur Mashita; Dwi Winarni (The East Java Biological Society, 2012)
This research aimed to know the bioactivity of polysaccharide krestin (PSK) with a different timing on formation of mice antibody exposed by Mycobacterium tuberculosis. Mycobacterium tuberculosis was used as infection agent that had an abilitiy to be imunogenic and to lead immune system responses decreased. Polysaccharides krestin was used as immunopotentiator which had a role to activate macrophage and stimulate B cell in order to produce antibody. This research involved 30 adult female mice of Mus musculus strain Balb/C in the age of 8–10 weeks and in the weight between of 30–40 g. Mice were divided into six groups, as follows: group K as a control, was added only aquades; group K+ as positive control, was added only PSK; group K- as negative control, was exposed by M. tuberculosis only; group P1 was added PSK before being exposed by M. tuberculosis; group P2 was added PSK after being exposed by M. tuberculosis; group P3 was added PSK before and after being exposed by M. tuberculosis. Polysaccharides krestin was added by gavage with single dose of 500 μg and M. tuberculosis was exposed intraperitoneally with concentration of 5x108 bactery per ml. The bioactivity of PSK was observed by formation antibody using indirect ELISA test. The results of research were the average of OD value of K group was 0,590 ± 0,042, K+ group was 0.641 ± 0.025, K- group was 1.044 ± 0.054, P1 group was 1.032 ± 0.125, P2 group was 1.127 ± 0.042, P3 group was 1.230 ± 0.097. The conclusion of this research showed that the adding of PSK increased mice formation antibody. The time of adding before and after being exposed M. tuberculosis was the most potential to raise antibody production on mice.